2019
DOI: 10.3390/f10121093
|View full text |Cite
|
Sign up to set email alerts
|

The Availability of Non-Timber Forest Products under Forest Succession on Abandoned Fields along the Wild Coast, South Africa

Abstract: Large swathes of arable fields have been abandoned in many areas of the world over the last few decades driven by a multitude of local and broader-scale factors. Many former fields experience a change in vegetation composition and structure post-abandonment, typically through a process of plant succession. The changes in species and abundance mean that the nature and quantity of ecosystem services provided by the former fields also varies. We examined the types of provisioning services obtained from non-timber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Our study findings suggest that historic deforestation and commercial selective logging likely had a large negative impact on the viability of these four species (Figure 2c), more so than contemporary informal forest resource harvesting, despite it being largely unregulated (Leaver & Cherry, 2020a, 2020bLeaver et al, 2019). The contemporary effective population sizes of all four species (Figure 2b; Table S2) are likely underestimates resulting from pooled generations (Luikart et al, 2010) (Njwaxu & Shackleton, 2019;Skowno et al, 2019;Stickler & Shackleton, 2014). But 63% of Albany thicket is severely degraded (14.0-25.4% valley thicket, and 12.8% mesic thicket) (Lloyd et al, 2002), and the extent of coastal thicket degradation is unknown.…”
Section: Population Viability and Effective Population Sizementioning
confidence: 72%
“…Our study findings suggest that historic deforestation and commercial selective logging likely had a large negative impact on the viability of these four species (Figure 2c), more so than contemporary informal forest resource harvesting, despite it being largely unregulated (Leaver & Cherry, 2020a, 2020bLeaver et al, 2019). The contemporary effective population sizes of all four species (Figure 2b; Table S2) are likely underestimates resulting from pooled generations (Luikart et al, 2010) (Njwaxu & Shackleton, 2019;Skowno et al, 2019;Stickler & Shackleton, 2014). But 63% of Albany thicket is severely degraded (14.0-25.4% valley thicket, and 12.8% mesic thicket) (Lloyd et al, 2002), and the extent of coastal thicket degradation is unknown.…”
Section: Population Viability and Effective Population Sizementioning
confidence: 72%
“…The municipal land use change analysis corroborated their reports. Land abandonment, which is followed by an increase in forest cover, has been reported in other parts of Mexico (GarcĂ­a-Barrios et al, 2009), in the Caribbean (Aide et al, 2000b;Timms et al, 2013), Central America (Kull et al, 2007), the Mediterranean (Malavasi et al, 2018), Asia (Ashraf et al, 2017) and Africa (Jacob et al, 2017;Njwaxu and Shackleton, 2019). At the household level, we observed that migration had a negative impact on agricultural activities.…”
Section: Assessing Multi-level Change: How Households and Landscape Trajectories Are Relatedsupporting
confidence: 62%
“…Many NTFPs are extracted from economically valuable tree species in primary forest, such as resin from trees of the family Dipterocarpaceae, orchids, and other wood extracts (De Beer and Mcdermott 1996). There are also many useful NTFP species common in secondary forest, such as bamboo, which is abundant in areas with high levels of forest degradation, and medicinal herbs, which are abundant in fallow fields (Njwaxu and Shackleton 2019).…”
Section: Discussionmentioning
confidence: 99%